Working with the National Student Clearinghouse to Learn about UW-Madison Students - Hull, Philip; Huhn, Clare (My University, 2007)
Originally created for determining federal student loan eligibility and deferment status, the National Student Clearinghouse (NSC) is a now massive database of enrollment and degree records submitted by over 2,800 participating colleges and universities. Covering over 90 percent of enrollments nationwide, it has evolved from a simple verification tool into a rich source of information for institutional and educational research. In this presentation, two campus staff with extensive experience with the NSC will highlight how UW-Madison is utilizing the database and what it can teach us about the university's applicants, students, and graduates.
Keywords: National Student Clearinghouse (NSC)